Observing Galaxy Clusters with eROSITA: Simulations - J. Hölzl; J. Wilms; I. Kreykenbohm; Ch. Schmid; Ch. Grossberger; M. Wille; W. Eikmann; T. Brand (Acta Polytechnica, 2011)
The eROSITA instrument on board the Russian Spectrum Roentgen Gamma spacecraft, which will be launched in 2013,will conduct an all sky survey in X-rays. A main objective of the survey is to observe galaxy clusters in order to constrain cosmological parameters and to obtain further knowledge about dark matter and dark energy. For the simulation of the eROSITA survey we present a Monte-Carlo code generating a mock catalogue of galaxy clusters distributed accordingto the mass function of [1]. The simulation generates the celestial coordinates as well as the cluster mass and redshift. From these parameters, the observed intensity and angular diameter are derived. These are used to scale Chandra cluster images as input for the survey-simulation.